CD-1 Mice Show Individual Differences in Nicotine Preference in a Modified Two-Bottle Oral Self-Administration Model - Cao, Junran; Gautier, Nicole M.; Li, Ming D. (Frontiers in Psychiatry, 2012)
Genetic epidemiology reveals significant contributions of genetics to smoking addiction. However, such study is underpowered because of the many potential confounding variables. These issues can be compensated for by a proper animal model. In the current study, we used non-sibling CD-1 mice to increase the genetic variation and evaluated nicotine preference in a modified two-bottle oral self-administration model. Animals were first given free access to two bottles, one filled with nicotine dissolved in 2% saccharin and the other with saccharin only. At this stage, the majority of animals avoided the nicotine solution with small individual differences. However, after four days of exposure to 5% saccharin in the drinking water, the ratio of nicotine consumption to total liquid consumption was significantly increased, and about 40% animals showed a nicotine preference. There were striking individual differences in nicotine consumption, with a range of 0 to 100% of total liquid consumption. Nicotine preference after 5% saccharin treatment remained elevated throughout the 28 days of experiment. The enhanced ratio of nicotine consumption and individual differences were observed at different concentrations of nicotine (10 to 80 µg/ml) and in both adolescents and adults. Although liquid consumption during the four days of 5% saccharin induction was decreased by about 30%, comparable liquid restriction alone for four days did not induce nicotine preference. The long-lasting nicotine preference was not correlated with nicotine consumption before the induction, 5% saccharin consumption, or weight gain during the induction. Together, this study showed a long-lasting nicotine preference in CD-1 mice, which was induced by a short-term high concentration of saccharin in the drinking water. We observed significant individual differences in nicotine consumption. Given the nature and heterogeneity of CD-1 mice, such striking individual differences indicate that genetics plays an im